Prevalence and Determinants of Oral Health Conditions Among Sicklers Aged 10-18 in Kisumu County, Kenya - Mosoti, Cliffland Mark (Amref International University, 2025)
Introduction: Sickle Cell Disease (SCD) poses a significant public health challenge in sub-Saharan Africa, with high prevalence among children in Kenya. Although oral health complications are common among individuals with SCD, they remain poorly documented, particularly in resource-limited settings. This study examined the prevalence and determinants of oral health conditions among children with SCD in Kisumu County. Methodology: A descriptive cross-sectional study was conducted among 355 children aged 10–18 years with SCD across six clinics in Kisumu County. Participants were selected through systematic sampling. Data were collected using structured questionnaires and clinical oral examinations, assessing caries through the DMFT/dmft index and plaque via Turesky’s modified plaque index. Analysis was performed using SPSS v30, with logistic and multiple regression models used to identify significant predictors. Results: Dental caries prevalence was 40%, and 98% of participants had plaque with a mean plaque score of 1.74 (0.8 SD), with 68.7% exhibiting moderate to severe levels. The mean DMFT score was 1.09, primarily driven by decayed teeth. Notably, 79.4% had never visited a dentist, and only 6.2% had received professional cleaning. Barriers to care were reported by 89.6% of participants, mainly due to high cost (51.8%) and facility inaccessibility (35.2%). Significant predictors of caries included sleep interference (OR = 0.04), limited access to dental facilities (OR = 0.25), and motivation to maintain healthy teeth (OR = 11.06). Plaque scores and DMFT were significantly associated with caregiver occupation, brushing frequency, fluoride use, and dental visit history. Conclusion: Oral health conditions are highly prevalent among children with SCD in Kisumu County and are strongly associated with limited access to care, low socioeconomic status, and inadequate self-care practices. Integrated oral health promotion and service delivery within SCD care programs are urgently needed.
A Research Thesis Submitted to The Department of Community Health, School of Public Health in Partial Fulfillment of The Requirements for The Degree of Master of Public Health (Applied Epidemiology) Amref International University
Keywords: Sickle Cell Disease